Ketiadaan Daluwarsa Penuntutan dalam Hukum Pidana Islam dan Pembaruan Hukum Pidana di Indonesia (UINSI Samarinda, 2016)
A statute of limitation is the passage of specified number of years that become the reason for abolishing of criminal penalties against someone who has committed a criminal act. Basically, all the perpetrators of criminal acts should be prosecuted in a criminal court to face trial, but there are things which abolish criminal prosecution such as the statute of limitation. In order to reform the criminal law, it must necessarily be carried out by reconstructing underlying ideas of such reformation, that is the materialization of justice. One of the ways to do so is by including the concept of absence of the statute of limitation as adopted by the concept of Islamic criminal law. This paper argues that the statute of limitation enshrined in the Criminal Code gives more emphasis on the rule of law, while the absence of the statute of limitation in the Islamic Criminal Law give more emphasis on the fairness and certainty. Achieving justice is not limited by time; whereas certainty is limited by the availability of valid evidence. To that end, the introduction of the concept of absence of statute of limitation into positive law is necessary to ensure that justice which is the main purpose of law enforcement. In addition, the introduction of this Islamic criminal law concept is also a strategic move to make Islamic law a part of the positive law in Indonesia.Keywords: A statute of limitation, Jinayah in Islam, criminal law in Indonesia